2019
DOI: 10.1371/journal.pone.0213712
|View full text |Cite
|
Sign up to set email alerts
|

RUPEE: A fast and accurate purely geometric protein structure search

Abstract: Given the close relationship between protein structure and function, protein structure searches have long played an established role in bioinformatics. Despite their maturity, existing protein structure searches either use simplifying assumptions or compromise between fast response times and quality of results. These limitations can prevent the easy and efficient exploration of relationships between protein structures, which is the norm in other areas of inquiry. To address these limitations we have developed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…We classified the 527 uncharacterized proteins by searching for similar structural folds and topologies in the SCOPe and CATH databases with RUPEE ( Fig. 1C; Table S3) (34)(35)(36). The classification identified enzymes of diverse functions.…”
Section: Structural Modeling Resolves a Large Subset Of Secreted Protmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified the 527 uncharacterized proteins by searching for similar structural folds and topologies in the SCOPe and CATH databases with RUPEE ( Fig. 1C; Table S3) (34)(35)(36). The classification identified enzymes of diverse functions.…”
Section: Structural Modeling Resolves a Large Subset Of Secreted Protmentioning
confidence: 99%
“…The secondary structures and disordered residues were predicted with PSIPRED v4.0 and DISOPRED v3.16 (105,106). The predicted structures were compared with RUPEE against the SCOPe v2.07 and CATH v4.2.0 databases as well as the PDB chains (TOP_ALIGNED, FULL_LENGTH) (27,(34)(35)(36). Regardless of the confidence scores, a top hit was reported.…”
Section: Functional and Structural Annotations Of The Secretomementioning
confidence: 99%
“…Even when a large enough MSA is available, AlphaFold as well as traditional physics-based approaches to protein structure prediction, such as Rosetta, 6 have not reached the desired level of accuracy. 3 Previously, we introduced RUPEE, 7 a purely geometric protein structure search with no dependence on sequences or clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Since the release of RUPEE, 7 we have observed that RUPEE has been used to upload protein structures that were the output of a protein structure prediction method in order to identify the most similar known structure to the predicted structures. For the most part, these uploaded protein structures have had low sequence and structure similarity to known structures in the PDB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation